Effect of plant-derived feed additives on enteric methane emission, nutrient digestibility and immune status of adult male goats - Kumari, N.; Kala, A.; Agarwal, N.; Chaturvedi, V.B.; Kennady, Vijayalakshmy; Chaudhary, L.C. (2025)
Ruminal methanogenesis reduces animal feed utilizing efficiency and is a potent greenhouse gas contributing to climate change. The present study aimed to study the effect of plant secondary metabolites on methane emission, nutrient digestibility and immune status of adult male goats. To fulfil the goal, 20 adult male goats (2.5−3 years of age, body weight [BW] 25.90 ± 1.46 kg) were divided into four groups of five animals. The control was fed a basal diet containing wheat straw and concentrate in a 50:50 ratio without additives. In groups T1, T2 and T3, the basal diet was supplemented with ajwain (Trachyspermum ammi) oil @ 0.06% dry matter intake (DMI), bahera (Terminalia belirica) @ 0.8% DMI and combination of ajwain oil and bahera @ 0.06% and 0.8% DMI, respectively. The DMI, nutrient digestibility, nitrogen intake, outgo and nitrogen balance were similar (p > 0.05) in all four groups. Methane emissions (g/kg DDMI) reduced (p < 0.05) by 22.16%, 23.88% and 33.49% in T1, T2 and T3 compared to control. Both cell-mediated immunity and humoral immune response significantly improved in T3 than other supplemented groups and control. In conclusion, the combination of behera and ajwain oil effectively reduced methane emissions and improved the immune status of adult male goats without affecting nutrient digestibility.